Evaluation of Non‐Ambiguous Critical Micelle Concentration of Surfactants in Relation to Solution Behaviors of Pure and Mixed Surfactant Systems: A Physicochemical Documentary and Analysis. Issue 4 (18th March 2021) - Moulik, Satya P.; Rakshit, Animesh K.; Naskar, Bappaditya
Abstract: Critical micelle concentration (CMC) is a fundamental physical parameter of surfactant aggregation in solution. The CMC is determined by different methods, tensiometry, conductometry, microcalorimetry, fluorimetry, and so on. However, it is known that though CMC is reported as a single value, in reality, micelle formation occurs over a narrow range of concentration for different experimental procedures produce different results. We shall discuss about a unique procedure of measuring correct CMC applicable to all potential methods used in practice. This is essential for the evaluation of thermodynamic properties of the micelle forming process in pure and mixed states in terms of solution theories. As we in this short documentary want to deal with various aspects of Milton Rosen's research—wherein we have also worked—a few other facets of surfactant chemistry research, besides the micelle formation, are also briefly discussed. In mixed surfactant systems, synergistic effects in various surfactant properties like detergency, foaming, solubilization, and so on are found whereas in some others non‐synergistic effects are observed. Dehydration of micelles with an increase in temperature or by the addition of hydrophilic substances may cause clouding to the system. Soluble amphiphilic systems produce Gibbs monolayer at the air/water interface; insoluble amphiphiles form Langmuir monolayers. A documentary of the above aspects will be herein presented and discussed. We mention that this article is neither an original research article nor a review article. This is a mixture of the two: a documentary of both original research and some review of our works presented in memory of Prof. Milton Rosen.